Nebivolol Monotherapy in Younger Adults (Younger Than 55 Years) With Hypertension: A Randomized, Placebo‐Controlled Trial. Issue 9 (16th July 2013) - Giles, Thomas D.; Khan, Bobby V.; Lato, June; Brener, Lillian; Ma, Yimin; Lukic, Tatjana
Abstract : Nebivolol, a vasodilatory β1 ‐blocker, may be well suited for the hemodynamics of the younger hypertensive patient. In this 8‐week trial, 18‐ to 54‐year‐olds with a diastolic blood pressure (DBP) of 95 mm Hg to 109 mm Hg who completed a 4‐week placebo‐only phase were randomized to receive nebivolol (5 mg/d, titrated to 10–20 mg/d based on achievement of blood pressure <140/90 mm Hg [n=427]) or placebo (n=214). Primary and secondary efficacy parameters were changes in trough seated DBP and systolic blood pressure (SBP), respectively. Safety parameters included adverse events (AEs). The baseline mean age was 45.3 years; SBP/DBP, 154/100 mm Hg; and heart rate, 78 beats per minute. Completion rates were 91.3% (nebivolol) and 88.3% (placebo). At endpoint, there was a significant effect of nebivolol over placebo for DBP (−11.8 mm Hg vs −5.5 mm Hg, P <.001) and SBP (−13.7 mm Hg vs −5.5 mm Hg, P <.001). Total AE rates were 34.7% (nebivolol) and 32.2% (placebo). Nebivolol monotherapy is efficacious and well tolerated in adults younger than 55 years of age with increased DBP.